Bringing terrorists to justice in the context of armed conflict: interaction between international humanitarian law and the un conventions against terrorism. - Sánchez-Frías, Alejandro (Cambridge University Press, 2019)
The participation of foreign fighters on the side of terrorist groups has raised many questions about the legal basis for the criminal prosecution of acts of terror during armed conflicts. In cases regarding the commission of terrorist crimes with transnational elements, such as the foreign nationality of the alleged perpetrator, cooperation with other states in matters such as extradition or mutual legal assistance can be crucial. This study will analyse two regimes that may constitute a legal basis for cooperation in criminal matters against acts of terror committed during armed conflicts: (i) the rules on criminal responsibility under international humanitarian law (IHL), and (ii) the United Nations framework of anti-terrorist conventions. IHL has been seen by many as the only framework applicable to acts committed during armed conflicts. In contrast, the position adopted in this article is that IHL does not necessarily exclude the application of other regimes to acts committed during armed conflicts, which can serve as a complementary tool in international efforts for the prevention and suppression of terrorism.
Keywords: Terrorismo; Derecho humanitario; Foreign terrorist fighters; Cooperation in criminal matters; International humanitarian law